Transhumanism and transcendence : Christian hope in an age of technological enhancement - Cole-Turner, Ronald, 1948- (Georgetown University Press, 2011)
The timeless human desire to be more beautiful, intelligent, healthy, athletic, or young has given rise in our time to technologies of human enhancement. Athletes use drugs to increase their strength or stamina; cosmetic surgery is widely used to improve physical appearance; millions of men take drugs like Viagra to enhance sexual performance. And today researchers are exploring technologies such as cell regeneration and implantable devices that interact directly with the brain. Some condemn these developments as a new kind of cheating -- not just in sports but in life itself -- promising rewa.